"It is not necessary to organize a trip to the moon": a mixed method study with mentors in the Italian Mentor-UP program during the COVID-19 pandemic. Issue 3 (27th May 2022) - Marino, Claudia; Gaboardi, Marta; Kaufman, Michelle R.; Bonichini, Sabrina; Bergamin, Marisa; Canale, Natale; Santinello, Massimo
ABSTRACT: This study used a mixed methods approach to explore the experience of mentors involved in the Mentor-UP program during the COVID-19 pandemic in Padova, Italy. In Study 1, a total of 53 mentors completed an online questionnaire at the end of the program. Results of the path analysis showed that mentors' perceived support from the program staff was associated with lower levels of psycho-physical burnout, which in turn was negatively associated with online communication frequency, and the latter was positively associated with mentoring relationship quality. Study 2 analyzed in more detail the mentor-mentee relationships during the pandemic and specifically how COVID-19 may have affected the program. Two online focus groups were conducted and transcripts analyzed using thematic analysis. Results indicated that online mentoring interactions, although different from face-to-face, were valuable and allowed the establishment of supportive relationships for youth. Findings suggest program staff should provide constant support to mentors.